Caracterización de deficiencias estructurales en construcción de viviendas sismorresistentes en El Mirador, Ciudad Bolívar, Bogotá. (2023)
The seismic vulnerability of a structure is the estimated damage, type of failure, and resistance capacity in the face of a probable earthquake magnitude that can occur due to the soil and tectonic conditions of the area. Given that the Mirador neighborhood is in Ciudad Bolívar, a town that has been populated without planning through informal settlements where the application of seismic regulations is lacking, despite the intermediate risk of the area and geological hazards, it is extremely important to determine the level of seismic vulnerability accurately to prevent significant material and human losses.